Stay-on-Task Exercises as a Tool To Maintain Focus during a CRISPR CURE - Ben A. Evans (American Society for Microbiology, 2021)
ABSTRACT Course-based undergraduate research experiences (CURE) offer the chance for students to experience authentic research investigation in a classroom setting. Such hands-on experiences afford unique opportunities work on a semi-independent research project in an efficient, structured environment. We have developed a CRISPR CURE in which undergraduate and graduate students use in silico, in vitro, and in vivo techniques to edit a fungal genome. During the development of this course, we have found that the asynchronous nature of the CRISPR CURE activities can be disruptive and lead to unproductive class time. To overcome this challenge, we have developed stay-on-task exercises (SOTEs). These short low-stakes assessments provide structured activities that are performed during these asynchronous incubation periods. SOTE activities leverage potentially unproductive class time and complement the CURE learning objectives. We have found SOTEs to be one method of maintaining classroom structure during a CURE. Furthermore, SOTE complexity, length, and subject can be easily modified to match course learning objectives.